2012
DOI: 10.1073/pnas.1212428109
|View full text |Cite
|
Sign up to set email alerts
|

Expression of plasma cell alloantigen 1 defines layered development of B-1a B-cell subsets with distinct innate-like functions

Abstract: Innate-like B-1a cells contribute significantly to circulating natural antibodies and mucosal immunity as well as to immunoregulation. Here we show that these classic functions of B-1a cells segregate between two unique subsets defined by expression of plasma cell alloantigen 1 (PC1), also known as ectonucleotide pyrophosphatase phosphodiesterase 1 (ENPP1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 65 publications
(63 reference statements)
6
57
2
Order By: Relevance
“…Rather, CD73 identifies a specific CD73 hi subset that differs little from CD73 − B-1 cells in many functional parameters with the notable exception of ectoezyme activity. However, CD73 expression is not the only surface antigen that distinguishes B-1 cell subpopulations, as B-1 cell phenotypic heterogeneity extends to expression of PD-L2 (45), CD80 (61), CD25 (47), PC1 (48) and CD5 (42). Interestingly, Shlomchik’s group recently reported that CD73, PD-L2 and CD80 are expressed by some memory B (Bmem) cells, suggesting that Bmem cells are phenotypically heterogeneous (50, 51), much like B-1 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, CD73 identifies a specific CD73 hi subset that differs little from CD73 − B-1 cells in many functional parameters with the notable exception of ectoezyme activity. However, CD73 expression is not the only surface antigen that distinguishes B-1 cell subpopulations, as B-1 cell phenotypic heterogeneity extends to expression of PD-L2 (45), CD80 (61), CD25 (47), PC1 (48) and CD5 (42). Interestingly, Shlomchik’s group recently reported that CD73, PD-L2 and CD80 are expressed by some memory B (Bmem) cells, suggesting that Bmem cells are phenotypically heterogeneous (50, 51), much like B-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…B-1a cells are the primary source of natural antibody which can also be contributed by marginal zone B cells whereas B-1b cells contribute long lasting memory to some kinds of bacteria or virus infections (43) (44). In addition to CD5, recent studies have revealed that B-1 cell populations can be subdivided based on the expression of PD-L2 (CD273) (45, 46), CD25 (47) and PC1 (also termed ENPP1) (48). It was originally reported that CD73 is expressed on a few mouse splenic B cells (49) and more recent data show that CD73 is expressed by memory B (Bmem) cells (50, 51).…”
Section: Introductionmentioning
confidence: 99%
“…The two classic functions of B-1a cells, i) innate-like and ii) immunoregulatory can be segregated between two unique subsets based on the expression of plasma cell alloantigen 1 (PC1), also known as ectonucleotide pyrophosphatase phosphodiesterase 1 (ENPP1), an enzyme involved primarily in the hydrolysis of ATP at the cell surface [59]. These subsets, designated B-1a.PC1 lo and B-1a.PC1 hi , express distinct IgH repertoires and contribute to varied levels of serum and mucosal natural Abs [59].…”
Section: B-1-related Cells and Subsets In Innate Immunitymentioning
confidence: 99%
“…reactive B cells versus regulatory B cells, and in the role that each of these subsets play at different stages of disease progression. While B effector cells seem to contribute to disease progression, regulatory B cells may be protective against disease initiation, including IL-10 producing B-cells [95]. …”
Section: 0 Near Future: the Immune Networkmentioning
confidence: 99%